Exploring the frontier of lung alveolar regeneration: Cellular dynamics, aging effects, and emerging therapeutics - Rashid A. Aldahhan; Amal Ahmed El-Sheikh (Translational Research in Anatomy)
Structured abstract: Background: Alveolar regeneration is essential for maintaining lung function and enabling recovery following lung injury. Impairment of this process contributes to the progression of various respiratory diseases. A detailed understanding of the cellular and molecular mechanisms driving alveolar repair is crucial for the development of effective therapeutic strategies. Methods: A literature search was conducted in PubMed, Scopus, and Google Scholar focusing on the history of alveolar regeneration and the cells involved in this process, the effects of aging, and associated therapeutic implications. The keywords used in the search included “alveolar regeneration,” “aging,” “cell senescence,” “stem cells,” “growth factors,” and “therapeutic potential.” Results: This review explores the key cellular players involved in alveolar repair, focusing particularly on alveolar type 2 cells and other progenitor populations that contribute to alveolar epithelial renewal. This review also highlights how aging affects regenerative capacity, as age-related cellular dysfunction may impair lung repair and exacerbate chronic pulmonary conditions. Furthermore, novel insights into alveolar regeneration are reviewed, including recent advancements in in vivo and in vitro models as well as single-cell technologies that provide a deeper understanding of the regenerative process. Emerging therapeutic strategies, such as stem cell–based therapies, gene editing, and pharmacological interventions, are also discussed in the context of enhancing alveolar regeneration. Conclusions: By integrating recent discoveries and identifying key knowledge gaps, this review provides a comprehensive overview of alveolar regeneration and emphasizes potential therapeutic approaches for promoting lung repair and restoring respiratory function.